Medicinal plants used by the Batak Toba Tribe in Peadundung Village, North Sumatra, Indonesia - MARINA SILALAHI; NISYAWATI NISYAWATI; DINGSE PANDIANGAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Silalahi M, Nisyawati, Pandiangan D. 2019. Medicinal plants used by the Batak Toba Tribe in Peadundung Village, North Sumatra, Indonesia. Biodiversitas 20: 510-525. Research of the medicinal plants by the Toba Batak ethnic has limited, even though the globalization and modernization resulted to degradation of the local knowledge. The objectives of this study were (i) documentation of medicinal plants used in the traditional therapies by the Batak Toba tribe of Peadundung Village, North Sumatra, Indonesia, and (ii) analysing the data by quantitative ethnobotanical tools such as use value (UV), cultural significance index (CSI), relative frequency of citation (RCF) and informant consensus factor (ICF) to determine the cultural importance of medicinal plants in order to develop a tool for their conservation. Semi-structured interviews with 41 identified respondents was the methodology employed for qualitative data collection. A total of 149 medicinal species of plants, belonging to 131 genera and 55 families, were recorded in the study which are used in the treatment of 21 categories of ailments. Plants with the highest UV were Eurycoma longifolia (UV=3.44), Curcuma longa (UV=2.67) and Zingiber officinale (UV=2.60). Eight species, namely Curcuma longa, Eurycoma longifolia, Allium cepa, Psidium guajava, Aleurites moluccanus, Piper betle, Citrus hystrix and Uncaria gambir were found to be having the highest RCF value of 1.00. Eurycoma longifolia (CSI=126), Curcuma longa (CSI=112) and Zingiber officinale (CSI = 105) emerged as the culturally most significant medicinal plants. Thrush and aphrodisiac use categories received the highest ICF of 1.00 each because the informants agreed of using only a single species for each of these categories. Eurycoma longifolia was used as an aphrodisiac whereas Averrhoa carambola was used against thrush. All these important and significant plants suffer the greatest harvesting pressure, hence their conservation should be given priority.